Neonatology b management, procedures, on-call problems, diseases, and drugs - Gomella, Tricia Lacy; Cunningham, M. Douglas; Eyal, Fabien G. (Fabien Gabriel) (McGraw-Hill Education Medical, 2013)
This 7th edition provides practical and easily accessible information on the basic and advanced management of the neonate in a logical outline approach. All neonatal procedures, disorders, and pharmacology are covered, highlighting essential information. Features: provides quick answers to both common and rare clinical issues; the popular "On-Call Problems" section details more than 30 of the most common and critical clinical conditions faced in the NICU; comprehensive pharmacology section includes indications and use, actions, means of delivery, dosages, possible adverse effects for over 150 drugs.